Gastrointestinal stromal tumor of the small bowel complicated by torsion: A case report. (November 2022) - Yoshizawa, Jun-ichi; Shimizu, Tadaaki; Ikehara, Tomohiko; Fukushima, Kentaro; Nakayama, Ataru
Abstract: Introduction: Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors that originate from the gastrointestinal tract wall. Approximately 20–30 % of GISTs originate from the small intestine. GISTs of the small intestine generally present with a palpable mass, distention, and abdominal pain and may exhibit acute abdomen at the onset. Herein, we describe a rare case of a pedunculated GIST of the small intestine complicated by torsion. Presentation of case: A 69-year-old woman presented with lower abdominal pain. Abdominal contrast-enhanced computed tomography showed a 73 × 62 × 57-mm 3 tumor in the pelvic cavity with enhanced margins and reduced contrast. It was presumed that the tumor had caused hemorrhagic infarction. Emergency laparotomy was performed, and the pedunculated tumor was found to be twisted 360° clockwise at the pedicle with hemorrhage and necrosis due to torsion. We performed partial resection of the small intestine including the tumor. Histopathological examination revealed tightly arranged spindle-shaped cells with hemorrhage, congestion, and inflammatory cell infiltration. Immunohistochemical staining showed positivity for CD34, CD117, and DOG1. Conclusions: Torsion of a pedunculated small intestine GIST, although very rare, requires emergency surgery and should be recognized as a cause of acute abdomen in patients with GIST. Immediate surgery is mandatory if torsion of a small intestinal GIST is suspected because the GIST or intestine may become necrotic owing to hemorrhagic infarction. Highlights: Pedunculated gastrointestinal stromal tumors (GISTs) with torsion are rare. Torsion of GISTs should be recognized as one of the causes of acute abdomen in patients with GIST. If a GIST has torsion and ischemic necrosis, the tumor will have no contrast effect inside on CT. Prompt surgery is vital if torsion of a small intestinal GIST is suspected.